Whither Nervous Shock? The Current State, Future Direction and Possible Reform of Compensation for Negligently Inflicted Psychiatric Injury after Ramstead - McRae, Peter Richmond (Victoria University of Wellington Law Review, 2001)
Whether compensation should be available for psychiatric injury, traditionally labelled "nervous shock", has been a vexed question whether considered by the courts or by regulatory bodies in terms of the Accident Compensation scheme. In this article, the author provides an analysis of the evolution of compensation for nervous shock in New Zealand, from its incorporation in the original Accident Compensation Act 1972, its release into tort by the 1992 Act and its subsequent development by the courts up until the Court of Appeal decision in Ramstead. The decision in Ramstead is then analysed, and its implications for the tort discussed in light of the United Kingdom and Australian jurisprudence. Ultimately, the author concludes that nervous shock is better dealt with under the statutory compensation scheme and canvasses the arguments made in support and against this proposition.